A system of assessing the severity degree of the foveal structural changes according to the data of spectral optic coherent tomography and visual acuity in the eyeball contusion (Ukrainian Journal of Ophthalmology, 2026)
Introduction: Blunt ocular injury is one of the serious problems in ophthalmology. Purpose: To study the grading system of structural changes in the fovea based on spectral optical coherence tomography and visual acuity after blunt eye injury. Material and methods: 43 patients with blunt ocular injury were observed. External nuclear layer, external limiting membrane, ellipsoid of the inner segments of photoreceptors, contact cylinder of cones, pigment retinal epithelium, examined by spectral optical coherence tomography and visual acuity were studied. We used cluster analysis for the grading system of structural changes in the fovea based on spectral optical coherence tomography and visual acuity after blunt eye injury. Results: We found 3 grades of structural changes in the fovea based on spectral optical coherence tomography and visual acuity after blunt eye injury mild, moderate, severe. Conclusion: The Grading system of structural changes in the fovea based on spectral optical coherence tomography and visual acuity after blunt eye injury showed 3 grades: mild, moderate, severe.
Keywords: fovea; structural changes; spectral optical coherence tomography; visual acuity; blunt ocular injury